A eutectic-alloy-infused soft actuator with sensing, tunable degrees of freedom, and stiffness properties. (9th January 2018) - Hao, Yufei; Wang, Tianmiao; Xie, Zhexin; Sun, Wenguang; Liu, Zemin; Fang, Xi; Yang, Minxuan; Wen, Li
Abstract: This paper presents a soft actuator embedded with two types of eutectic alloys which enable sensing, tunable mechanical degrees of freedom (DOF), and variable stiffness properties. To modulate the stiffness of the actuator, we embedded a low melting point alloy (LMPA) in the bottom portion of the soft actuator. Different sections of the LMPA could be selectively melted by the Ni–Cr wires twined underneath. To acquire the curvature information, EGaIn (eutectic gallium indium) was infused into a microchannel surrounding the chambers of the soft actuator. Systematic experiments were performed to characterize the stiffness, tunable DOF, and sensing the bending curvature. We found that the average bending force and elasticity modulus could be increased about 35 and 4000 times, respectively, with the LMPA in a solid state. The entire LMPA could be melted from a solid to a liquid state within 12 s. In particular, up to six different motion patterns could be achieved under each pneumatic pressure of the soft actuator. Furthermore, the kinematics of the actuator under different motion patterns could be obtained by a mathematical model whose input was provided by the EGaIn sensor. For demonstration purposes, a two-fingered gripper was fabricated to grasp various objects by adjusting the DOF and mechanical stiffness.